2013
DOI: 10.1007/s12291-013-0349-5
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Micronutrient Status in Compensated and Decompensated Liver Cirrhosis

Abstract: Decompensation followed by death is the most serious outcome in patients suffering from cirrhosis of the liver. Alteration of trace elements may play a vital role in the process of decompensation. To examine the change in status of trace elements during the decompensation process, we analysed the zinc, copper, iron, magnesium, bilirubin and albumin levels in the serum of compensated (n = 34) and decompensated (n = 31) liver cirrhosis patients and compared them with healthy control group (n = 36) by post hoc AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…A recent study compared serum trace element levels in patients with compensated versus decompensated liver cirrhosis. Zn levels were lower in the decompensated group 64 . In a placebo‐controlled trial of Zn treatment of patients with liver cirrhosis, hyperammonemia, and hypozincemia, a significant reduction in ammonia levels was observed in the treatment group 65 .…”
Section: Zn Deficiencymentioning
confidence: 93%
“…A recent study compared serum trace element levels in patients with compensated versus decompensated liver cirrhosis. Zn levels were lower in the decompensated group 64 . In a placebo‐controlled trial of Zn treatment of patients with liver cirrhosis, hyperammonemia, and hypozincemia, a significant reduction in ammonia levels was observed in the treatment group 65 .…”
Section: Zn Deficiencymentioning
confidence: 93%
“…Two studies have found that magnesium concentration was not significantly different between patients with and without liver cirrhosis and no significant correlation was found with the Child-Pugh score[ 109 , 110 ]. One study found magnesium levels were significantly lower in cirrhotic patients compared to controls, but there was no difference between compensated and decompensated patients[ 111 ]. Conversely, another study demonstrated a negative correlation between serum magnesium and Child-Pugh score, and lower levels of magnesium among patients with cirrhosis compared to controls[ 112 ].…”
Section: Micronutrient Status and Recommended Supplementation In Patimentioning
confidence: 99%
“…They analyzed magnesium levels in the serum of compensated (n=34) and decompensated (n=31) liver cirrhosis patients and compared with that of healthy control group (n=36) by post hoc ANOVA. Although a significant decrease in serum magnesium levels was found in cirrhosis patients overall (both Group I and 2) in comparison to the control subjects (p<0.05), no such difference was observed between the compensated and decompensated groups within the case population (p>0.05) [12].…”
Section: Discussionmentioning
confidence: 75%